Synthesis of Spin Coated Tungsten Oxide for Photocatalytic Degradation of Rhodamine-B Dye - Patil, P.S.; Kulkarni, A.N.; Khairnar, S.D.; Raghuwanshi, M.G. (Asian Journal of Chemistry, 2020)
Optical properties including band gap of many wide band gap semiconductor oxides like TiO2, ZnO and SnO2 has limitations over their bare use in photocatalytic applications. Thus, in view of above, tungsten oxide (WO3), an intermediate band gap metal oxide has been selected to explore for photocatalytic degradation application. Present work deals with the preparation of WO3 using a simple chemical solution based spin coating method. The prepared sample has been characterized for structural, morphological and photocatalytic properties. Degradation experiment of dye was carried out systematically at the optimized conditions of pH 4 and contact time (120 min) between dye and catalyst. For optimized conditions, WO3 showed about 75% of degradation of rhodamine-B. This suggests that a huge scope to optimize preparative parameters for WO3 to explore it as an alternative to conventional metal oxides.